Neutrophil to lymphocyte ratio as an indicative of diabetic control level in type 2 diabetes mellitus - Duman, Tuba T; Aktas, Gulali; Atak, Burcin M; Kocak, Mehmet Z; Erkus, Edip; Savli, Haluk (African health sciences, 2019)
Background: Type 2 diabetes mellitus is associated with chronic low grade inflammation. One of the novel inflammatory markers is hemogram derived neutrophil to lymphocyte ratio (NLR). Objective: We aimed to compare NLR levels of diabetic subjects and healthy controls and to observe possible correlation between NLR and HbA1c. Methods: Medical data of type 2 diabetic subjects admitted to out-patient clinics of our institution between April to July in 2017 were obtained from database and retrospectively analyzed. Control group was chosen from healthy subjects who visited our institution for a routine check-up. Anthropometric measures, laboratory data, including, HbA1c, NLR were recorded. Results: Median NLR of the type 2 DM group 2.44 (1.9) was significantly elevated when compared to healthy controls (1.5 (0.9), (p<0.001). In addition, a Pearson's correlation test revealed that NLR was strongly correlated with age (r=0.26, p=0.008), fasting plasma glucose (r=0.38, p<0.001), and HbA1c (r=0.49, p<0.001). Conclusion: Elevated NLR in otherwise healthy subjects may be indicative of underlying impaired glucose metabolism and moreover, NLR should be used as a marker of diabetic control level in addition to HbA1c in type 2 diabetic subjects. DOI: https://dx.doi.org/10.4314/ahs.v19i1.35 Cite as: Duman TT, Aktas G, Atak BM, Kocak MZ, Erkus E, H S. Neutrophil to lymphocyte ratio as an indicative of diabetic control level in type 2 diabetes mellitus. Afri Health Sci. 2019;19(1). 1602-1606. https://dx.doi.org/10.4314/ahs.v19i1.35